2020
DOI: 10.1002/er.5001
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanocomposite membranes based on PBI and doped‐perovskite nanoparticles as a strategy for improving PEMFC performance at high temperatures

Abstract: Summary In this work, Sr2+ dopant effects of Ba0.9Sr0.1TiO3 and La0.9Sr0.1CrO3‐δ doped‐perovskite nanoparticles on increasing proton conductivity, fuel cell performance, and mechanical and thermal stability of polybenzimidazole‐based nanocomposite membranes were studied. The Sr2+ dopant creates cation vacancies in Ba0.9Sr0.1TiO3 doped‐perovskite nanoparticles and oxygen vacancies in La0.9Sr0.1CrO3‐δ doped‐perovskite nanoparticles. The oxygen vacancies, which decrease columbic repulsion between protons and posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Therefore considering the defect density value of 10 13 cm −3 , the simulated results suggest that the highest efficiency that can be achieved with the planar perovskite solar cell configuration FTO/c-TiO 2 (20 nm)/Cs 2 Ti 0.25 Sn 0.75 Br 6 (600 nm)/Cu 2 O (200 nm)/Au is 22.13%. These results are based on a lead-free environmental friendly composition Cs 2 Ti 0.25 Sn 0.75 Br 6 and these results could be perceived as significant information for the development of future eco-friendly perovskite solar cells 9,46 as the perovskite solar cells without 'Pb' as the 'B' metal cation in perovskite matrix were unable to achieve such high efficiencies.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore considering the defect density value of 10 13 cm −3 , the simulated results suggest that the highest efficiency that can be achieved with the planar perovskite solar cell configuration FTO/c-TiO 2 (20 nm)/Cs 2 Ti 0.25 Sn 0.75 Br 6 (600 nm)/Cu 2 O (200 nm)/Au is 22.13%. These results are based on a lead-free environmental friendly composition Cs 2 Ti 0.25 Sn 0.75 Br 6 and these results could be perceived as significant information for the development of future eco-friendly perovskite solar cells 9,46 as the perovskite solar cells without 'Pb' as the 'B' metal cation in perovskite matrix were unable to achieve such high efficiencies.…”
Section: Resultsmentioning
confidence: 89%
“…Many attempts have been made to design efficient perovskite solar absorbers, however, the challenges such as toxicity, instability against moisture and temperature, unsuitable indirect band gap, and so on still prevail 1‐8 . Previous studies have reported environmentally benign perovskites 9,10 but the power conversion efficiency (PCE) remains low or suffers rapid degradation over time 11‐13 . The fully inorganic vacancy ordered caesium titanium‐based perovskite Cs 2 TiBr 6 reportedly have shown stability against heat and moisture with promising efficiency of ~3.3% 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Figure 5B shows the main effect plot for residual percentage. It reveals that by increasing the amount of CPVC, the oxidative stability of membranes decreases as by increasing percentage of CPVC hydrocarbon backbone increases which is prone to the attack of free radicals such as hydroperoxy ( ● OOH) and hydroxy ( ● OH) radicals 57,58 . However, by increasing the amount of PAMPS‐mGO, the oxidative stability of membrane increases due to the stable nature of GO sheets.…”
Section: Resultsmentioning
confidence: 99%
“…It reveals that by increasing the amount of CPVC, the oxidative stability of membranes decreases as by increasing percentage of CPVC hydrocarbon backbone increases which is prone to the attack of free radicals such as hydroperoxy ( • OOH) and hydroxy ( • OH) radicals. 57,58 However, by increasing the amount of PAMPS-mGO, the oxidative stability of membrane increases due to the stable nature of GO sheets. Furthermore, the oxygen-containing functionalities of GO offer extensive hydrogen bonding with the polymeric membrane and lead to compact membrane.…”
Section: Physiochemical Properties Of Membranementioning
confidence: 99%
“…At present, the most widely used PEMs is the Nafion membrane of DuPont Company. However, due to the high price of Nafion membrane, scientists are actively seeking alternative materials to Nafion membrane, such as sulfonated poly (aryl ether)s (Hooshyari et al, 2020 ). The introduction of sulfonic acid group can obviously improve the conductivity of membranes.…”
Section: Introductionmentioning
confidence: 99%